Function, occurrence and inhibition of different forms of BAFF. (August 2021) - Eslami, Mahya; Schneider, Pascal
Abstract : B cell activating factor (BAFF or BLyS), an important cytokine for B cell survival and humoral immune responses, is targeted in the clinic for the treatment of systemic lupus erythematosus. This review focuses on the structure, function and inhibition profiles of membrane-bound BAFF, soluble BAFF 3-mer and soluble BAFF 60-mer, all of which have distinct properties. BAFF contains a loop region not required for receptor binding but essential for receptor activation via promotion of BAFF-to-BAFF contacts. This loop region additionally allows formation of BAFF 60-mer, in which epitopes of the BAFF inhibitor belimumab are inaccessible. If 60-mer forms in humans, it is predicted to be short-lived and to act locally because adult serum contains a BAFF 60-mer dissociating activity. Cord blood contains elevated levels of BAFF, part of which displays attributes of 60-mer, suggesting a role for this form of BAFF in the development of foetal or neonate B cells.